Analisis Rentabilitas Usahatani Jagung Hibrida di Desa Sendangmulyo Kecamatan Bulu Kabupaten Rembang - Selawati, Dita; Setiadi, Agus; Ekowati, Titik (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2025)
The profitability analysis was conducted to determine the level of efficiency of the use of business capital in generating decent profits, so that it can continue to be developed until now. This study aims to analyze profitability and analyze the differences in profitability of hybrid corn farming in Sendangmulyo Village, Bulu District, Rembang Regency based on land area strata. This study was conducted in February - March 2025 in Sendangmulyo Village, Bulu District, Rembang Regency. The research method used a survey of 100 hybrid corn farmers of GAPOKTAN Tani Subur in Sendangmulyo Village, Bulu District, Rembang Regency. Sampling used a stratified random sampling technique based on land area strata, namely strata I, II, and III. The data analysis method used quantitative descriptive analysis of the financial conditions of the farm. The results of the study showed that the average profitability of equity and the economy of hybrid corn farming during one planting season was 33% and 30%, respectively, meaning it was greater than the BRI credit interest rate (6%), so it was feasible and profitable to pursue. In addition, there are differences in the profitability of hybrid corn farming capital in Sendangmulyo Village between strata I, II, and III which are described, including strata I with II, II with III, and I with III with each significance value <0.05, namely 0.000 <0.05, 0.000 <0.05, and 0.000 <0.05. The difference in economic profitability between strata I, II, and III shows that there is no difference, with details that there is no difference in RE in strata I with II (0.947> 0.05), while between strata II with III (0.049 <0.05) and I with III (0.040 <0.05) shows that there is a significant difference in RE value between strata of land area.